2012
DOI: 10.1002/stem.1081
|View full text |Cite
|
Sign up to set email alerts
|

Polo-Like Kinase 1 Inhibition Kills Glioblastoma Multiforme Brain Tumor Cells in Part Through Loss of SOX2 and Delays Tumor Progression in Mice

Abstract: Glioblastoma multiforme (GBM) ranks among the deadliest types of cancer and given these new therapies are urgently needed. To identify molecular targets, we queried a microarray profiling 467 human GBMs and discovered that polo-like kinase 1 (PLK1) was highly expressed in these tumors and that it clustered with the proliferative subtype. Patients with PLK1-high tumors were more likely to die from their disease suggesting that current therapies are inactive against such tumors. This prompted us to examine its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 84 publications
(106 reference statements)
6
61
0
Order By: Relevance
“…None of these trials have specifically addressed the possibility that PLK1 inhibitors may be beneficial for the treatment of brain tumors. Our group has demonstrated that PLK1 inhibitors could be used to target glioblastoma (18,40) and another group has published data agreeing with our findings in medulloblastoma (41,42). We illustrate that PLK1 is a promising drug target for medulloblastoma because (i) it is highly expressed in tumors relative to normal brain tissues and (ii) there are small molecule inhibitors that suppress primary medulloblastoma cells and cell lines in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…None of these trials have specifically addressed the possibility that PLK1 inhibitors may be beneficial for the treatment of brain tumors. Our group has demonstrated that PLK1 inhibitors could be used to target glioblastoma (18,40) and another group has published data agreeing with our findings in medulloblastoma (41,42). We illustrate that PLK1 is a promising drug target for medulloblastoma because (i) it is highly expressed in tumors relative to normal brain tissues and (ii) there are small molecule inhibitors that suppress primary medulloblastoma cells and cell lines in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 82%
“…Primary brain tumor cells were isolated from BTX001 (SHH), BT006 (SHH), BT007 (SHH), BT008 (PNET), BT014 (Group 4), BT274 (SHH), and BT025 (Group 4) and were grown as neurospheres as previously described (17) using Neurocult media (StemCell Technologies; ref. 18). All primary cells were obtained through informed consent in abidance with the respective research ethics board guidelines at British Columbia Children's Hospital and The Hospital for Sick Children.…”
Section: Cell Culture and Tumorsphere Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Plk1 expression is increased in a manner correlated with degree of anaplasia in human glioma cell lines [187]. Similarly, astrocytoma TPC show an increase in the expression of Plk1 more than 100 fold above that evident for non-neoplastic astrocytes [188]. Furthermore, inhibition of Plk1 in these TPC decreased proliferation and caused G2/M arrest, ultimately leading to apoptosis [188].…”
Section: Tumor Propagating Cellsmentioning
confidence: 99%